2017
DOI: 10.1016/j.ijom.2017.02.1263
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal ossification of the hyoid bone in cleidocranial dysplasia rare case and literature review

Abstract: Background: Centralisation of health care services has been one of the recent developments in the field of health policy. The aim of such projects is to improve the quality of the services provided to the patients and to achieve more efficient cost allocations. Objectives: In this study we aim to examine the costs incurred by the centralisation of head and neck cancer surgery from a peripheral London Hospital (Chase Farm Hospital) to University College London Hospital (UCLH) Head and Neck Department. We then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Conversely, the hyoid bone has been shown to have a more superior and posterior position in patients with hyperdivergent vertical facial growth [ 45 ]. In a 15-year-old boy patient with cleidocranial dysplasia, Yoshida et al reported a unique case of abnormal ossification of the hyoid bone [ 46 ]. Cephalometry of children with 22q11.2 deletion syndrome revealed a reduction of hyoid bone lengths, and hyoidal gaps, which reflect the fusion of the hyoidal segments, the greater horns, and the body, were larger than those of the controls [ 47 ].…”
Section: Anatomy and Fate Of Pharyngeal Archesmentioning
confidence: 99%
“…Conversely, the hyoid bone has been shown to have a more superior and posterior position in patients with hyperdivergent vertical facial growth [ 45 ]. In a 15-year-old boy patient with cleidocranial dysplasia, Yoshida et al reported a unique case of abnormal ossification of the hyoid bone [ 46 ]. Cephalometry of children with 22q11.2 deletion syndrome revealed a reduction of hyoid bone lengths, and hyoidal gaps, which reflect the fusion of the hyoidal segments, the greater horns, and the body, were larger than those of the controls [ 47 ].…”
Section: Anatomy and Fate Of Pharyngeal Archesmentioning
confidence: 99%